A SINGLE-ROW SUTURE IN SURGERY OF THE GASTROINTESTINAL TRACT - Mavlyanov, O.R.; Ataliev, A.E.; Mavlyanov, J.A; Babajonov, A.B.; Yusupbekov, D.A; Nurmatov, S.I (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The widespread introduction of devices for various mechanical sutures, the advantages of which are hardly in doubt, was a significant breakthrough in gastrointestinal surgery. However, the high cost and inaccessibility of the use of widely advertised hardware sutures, forced to still apply hand sutures with the most modern suture materials. The best suture is the one to which the surgeon is accustomed to and whom he has a good command, so it is difficult to convince supporters of 2 or 3 row sutures in the advantages of single row. The paper presents overview data on the use of various variants and modifications of a single-row suture in gastrointestinal surgery, their positive and negative sides, the frequency of complications and their causes.